Peran Pemangku Adat Suku Tengger dalam Menjalankan Sistem Hukum Adat - Fatmawati Fatmawati (JURNAL RECHTENS, 2016)
Advances in science and technology has led to erosion of the values of the authenticity of the Indonesian nation, known as the number of local wisdom. Indigenous peoples Tengger Wonokitri Village is a village where people are obedient to the positive law in Indonesia as well as keep the Law of indigenous patrimony. They were led by a Shaman or customary holders who chaired the Tengger community as a big family led social life, maintain and protect the lives of law to run it properly. Chairman of the joint indigenous people routinely hold salvation always known by the village or ceremonial "Entas-Entas" and "Indigenous Mayu" that has always existed existence until hereditary. Traditional authorities play a role over the actions of the customs and worship, as well as the legal act that is a crime, marriage, inheritance and land affairs related to the close affinity between the land and indigenous peoples. Customary law society Tengger tribe is able to synchronize and synergize well against positive law in Indonesia. The society is able to open up and adopt its rules of customary law from the outside if a positive impact on society. Activities traditional authorities aided by assistants (comprised of elderly or legen wong) the problems that occur in the community.